Analysis of Parental Involvement in Supporting The Effectiveness of Children's Swimming Training - JEJE, JENNYCA; Hadi, Hadi; Yudhistira, Dewangga (Universitas Negeri Semarang, 2024)
The aim of this study was to assess the significance of the involvement of parents, students and coaches in increasing the effectiveness of children's swimming training. The method used in this research is a qualitative descriptive method. The population used is the parents of the Gaussian Kamil School Swimming Club. Data collection in this study used interview and documentation techniques. The results of this study are in the form of a statement from a parent who definitely wants their child to be brave and improve their skills in swimming, and a child who enjoys practicing swimming with the role of their parents by providing encouragement while practicing. Based on the results of the interview study, it can be found that children will be confident and practice seriously when they are given encouragement such as motivational encouragement and moral support. Many parents are also proud when they see their child's skills improving from the beginning when their child was still learning to swim until now they can master all swimming styles in a few years. It can be concluded that the role of parents greatly supports the effectiveness of children's swimming, especially in supporting the development of children's skills and mentality, especially in the scope of children's swimming practice with new people.